ETHNOTOURISM OPPORTUNITIES IN NEW KARAKALPASTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article examines the development of ethnotourism in New Uzbekistan, with a focus on Karakalpakstan, within the framework of the "New Development Strategy for 2022-2026", which aims to attract 9 million foreign tourists annually. The study analyzes the role of museums and traditional handicrafts in promoting ethnic tourism, drawing on statistical data showing 118,000 foreign visitors to Karakalpakstan in 2023. The article traces the historical continuity of craftsmanship from the 19th century, when 1,445 artisans worked in the Amu Darya region, to contemporary initiatives such as the establishment of "Craftsmen's Town" in Ellikkala district and ethnographic villages near Nukus. Special attention is given to the revival of traditional Karakalpak crafts including yurt construction, carpet weaving, and textile production of "kok koylek" fabric. The research highlights successful examples of integrating handicraft workshops with tourism infrastructure, particularly A. Turekeev's family workshop-hotel-museum complex in Chimboy district. The article concludes with practical recommendations for developing ethnotourism through establishing specialized handicraft museums, creating "live exhibits" in craft workshops, and expanding tourist services in Karakalpak ethno-villages.